INNOVATION RECOGNITION, INDIVIDUAL PROGRESS AND IMPLICATIONS OF BEHAVIORAL CONTROL FOR ONLINE PURCHASE CHOICES - Mohammad Rafli Septian; Alshaf Pebrianggara; Andry Rachmadhany; Bayu Hari Prasojo (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the influence of behavioral control model, personal innovation, and technology adoption on Shopee purchase intention. Method: Data from 96 respondents were collected using the quantitative research design using SmartPLS software through surveys sent to the user platform Shopee. Results: These results indicate a positive relationship between the technology acceptance model, personal innovativeness, and behavioral control factors and how these factors influence purchase intention. Novelty: These findings highlight the importance of implementing a technology adoption model, consumer creativity, and efficient behavior management through the Shopee platform to increase purchase intention among platform users. The significance of this study is that it contributes to consumers' understanding of online product and service purchases and helps researchers develop strategies to increase customer engagement and satisfaction.